Decision Support An Examination of the DSS Discipline - Schuff, David; Paradice, David; Burstein, Frada; Power, Daniel J.; Sharda, Ramesh; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Foreword David Schuff, David Paradice, Frada Burstein, Daniel J. Power, and Ramesh Sharda Chapter 1: GDSS Past, Present, and Future Paul Gray, Bob Johansen, Jay Nunamaker, Jeff Rodman, and Gerald R. Wagner Chapter 2: Reflections on the Past and Future of Decision Support Systems: Perspective of Eleven Pioneers Frada Burstein, Dan Powers, and Ramesh Sharda Chapter 3: The Intellectual Structure of Decision Support Systems Research (1991-2004) Sean Eom Chapter 4: Ethical Decision-Making and Implications for Decision Support John R. Drake, Dianne J. Hall, and Teresa Lang Chapter 5: Web and Mobile Spatial Decision Support as Innovations: Comparison of United States and Hong Kong, China James B. Pick Chapter 6: Knowledge Management Capability in Education Jeremy Hodges and Ronald Freeze Chapter 7: Knowledge Warehouse Design for Decision Support in Critical Business Processes: Conceptual Modeling and Requirements Elicitation Meira Levy, Nava Pliskin, and Gilad Ravid Chapter 8: Agent-based Modeling and Simulation as a Tool for Decision Support for Managing Patient Falls in a Dynamic Hospital Setting Gokul Bhandari, Ziad Kobti, Anne Snowdon, Ashish Nakhwal, Shamual Rahaman, and Carol Kolga Chapter 9: Context-aware Mobile Medical Emergency Management Decision Support System for Safe Transportation Frada Burstein, Pari Delir Haghighi, and Arkady Zaslavsky Chapter 10: General Motors Bailout Problem: A Teaching Case Using the Planners LabTM Software Jim Courtney, Kristen Brewer, Randy Kuhn, and Gerald R. Wagner Chapter 11: Assessing Today: Determining the Value of Decision Support Systems Gloria Phillips-Wren, Manuel Mora, and Guisseppi Forgionne
Foreword -- Chapter 1: GDSS Past, Present, and Future -- Chapter 2: Reflections on the Past and Future of Decision Support Systems: Perspective of Eleven Pioneers -- Chapter 3: The Intellectual Structure of Decision Support Systems Research (1991-2004) -- Chapter 4 -- Ethical Decision-Making and Implications for Decision Support -- Chapter 5: Web and Mobile Spatial Decision Support as Innovations: Comparison of United States and Hong Kong, China -- Chapter 6: Knowledge Management Capability in Education -- Chapter 7: Knowledge Warehouse Design for Decision Support in Critical Business Processes: Conceptual Modeling and Requirements Elicitation -- Chapter 8: Agent-based Modeling and Simulation as a Tool for Decision Support for Managing Patient Falls in a Dynamic Hospital Setting -- Chapter 9: Context-aware Mobile Medical Emergency Management Decision Support System for Safe Transportation -- Chapter 10: General Motors Bailout Problem: A Teaching Case Using the Planners Lab$1!" (BSoftware -- Chapter 11: Assessing Today: Determining the Value of Decision Support Systems.s
Keywords: Economics; Information systems; Information Systems; Management information systems; Economics/Management Science; Operations Research/Decision Theory; Business Information Systems; Information Systems and Communication Service; Management of Computing and Information Systems